The strata management tribunal: a new dimension of Malaysian strata titles law - Sufian, Azlinor; Mohamad, Nor Asiah; Mustafa, Maizatun; Syed Abdul Kader, Sharifah Zubaidah (2013)
The strata titles law in Peninsular Malaysia has been first embodied in its own statute namely the Strata Titles Act, 1965. Prior to the enforcement of this main statute, the law on sub-divided buildings stood as part of the types of titles in the National Land Code, 1965 which was known as “subsidiary title”. The Strata Titles Act, 1965 may be regarded as the move towards having a more comprehensive law relating to the issuance of strata titles as well as the management of strata buildings. Under the Strata Titles Act, 1985, there exists the Strata Titles Board which was supposed to be the mechanism to settle disputes arising from issues relating to management of strata title buildings and facilities. Nevertheless the Strata Titles Board was not properly utilised and thus there were many problems on management of strata title buildings. Consequently the Building and Common Property (Management and Maintenance) Act, 2007 has been enforced though its effectiveness is somewhat questionable. Thus for those who cannot resolve their disputes amicably (for instance between a unit owner and a developer), claims may be filed before the ordinary courts. In lieu of this, the newly passed bill i.e. the Strata Management Bill 2012 (“SMB”) establishes a Strata Management Tribunal (“SMT”) with the aim to be an administrative forum to hear claims relating to maintenance and management of strata title buildings. The objective of this paper is to evaluate selected SMT provisions and to discuss whether this Tribunal would be the effective mechanism to resolve problems related to strata title buildings. This paper is prepared by utilising the qualitative approach. The findings suggest that there are a few provisions of the SMB and SMT that needs to be improved.